Attitude of Prime-Pregnant women toward Normal Vaginal Delivery in Southern of Babylon Governorate - Maryam Abd Al-Kareem1 , Salma Kadhum2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Normal vaginal delivery occurs when the mother birth of the fetus through vaginal canal, during this kindof birth mode, gravid women take special classes about labor and delivery process, how to prepared forit and learn the ways that lead to cope with the fear, anxiety and pain. Descriptive study cross sectionaldesign, the study carried out to identify the attitude of prime-pregnant women regarding normal vaginaldelivery in southern of Babylon governorate in Iraq. The results show (39.5%) as a highest percentage ofstudy sample at age ranging between (19-22) and more of them (33.0%) with secondary school as levelof education, also the assessment of response rate for prime pregnant women regarding overall domain ofnormal vaginal delivery was (Positive) for attitude regarding physiological delivery at mean of score (2.46)and attitudes regarding perceived behavioral control of normal vaginal delivery at mean of score (2.39)while the assessment of attitudes regarding personal and practical choice and sources of motivation was (Notsure) at mean of score (2.12).